EXTH-76. DEVELOPING THE NOVEL COMBINATION THERAPY OPTIONS FOR CANCER THERAPY USING TUMOR TREATING FIELDS TOGETHER WITH THE CHEMO AGENTS TARGETING THE REPLICATION STRESS PATHWAY. (12th November 2021) - Karanam, Narasimha Kumar; Story, Michael
Abstract: Tumor Treating Fields (TTFields) as a component of cancer therapy has been shown to provide significant clinical benefit. The disruption of mitosis was identified as the first mechanism of action, however, a novel role for TTFields outside of mitosis where TTFields downregulates the Fanconi's Anemia genes and proteins results in replication stress and reduced DNA repair capacity. Given these results we hypothesized that TTFields would increase the sensitivity of tumor cells to chemotherapy agents that increase replication stress. An analysis of agents that target replication stress in different ways was initiated. PARP1: Targeting PARP1 protects DNA breaks by recruiting DNA repair and checkpoint proteins to the sites of damage. Using the PARP1 inhibitor olaparib followed by radiation resulted in synergistic cell killing compared to radiation or olaparib alone or in combination. Etoposide: Etoposide forms a ternary complex with topoisomerase II and prevents re-ligation of DNA strands to elicit DNA strand breaks and replication stress. When combined with TTFields cell killing increased synergistically vs. etoposide alone. AZD6738: ATR is an essential kinase regulator of the replication checkpoint that plays a critical role in safeguarding genome integrity from replication stress. The advantage of combining TTFields with the ATR inhibitor- AZD6738 was tested for cell killing and the combination vs. AZD6738 was found to be synergistic. Irinotecan: Irinotecan traps topoisomerase I- DNA in a ternary cleavage complex and inhibits the initial cleavage reaction and re-ligation steps resulting in increased replication stress. Irinotecan and TTFields was tested and found to be highly effective at tumor cell killing. Collectively, our results suggest that it is likely of considerable clinical benefit to combine TTFields with chemotherapy agents that cause replication stress. This notion may explain the results of a number of clinical trials and suggests that there may be novel TTFields/replication stress-inducing chemotherapy agent combinations worth exploring.